Reduction of ammonia loss from urea through mixing with humic acids isolated from peat soil (saprists) - Bernard, Regis; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad; Jalloh, Mohamadu Boyie (Science Publications, 2009)
Problem statement: Application of urea as a source of nitrogen fertilizer has an adverse effect on ammoniacal loss to the environment. This study was conducted to reduce ammonia loss from urea by mixing with Humic Acids (HA) isolated from Saprists peat. Approach: The effects of urea amended with four different amounts of humic acids, 0.25, 0.50, 0.75 and 1.00 g were evaluated in laboratory conditions using a closed dynamic air flow system. The mineral soil that was used as medium for the study was Bekenu series (typic paleudults). Amnonia loss, soil pH, exchangeable ammonium, available nitrate, exchangeable K, Ca, Mg and Na were determined using standard procedures. Results: All the treatments with HA significantly reduced ammoinia loss compared to urea alone. Increasing the amount of HA also significantly retained soil exchangeable ammonium and available nitrate. Treatments with HA had no significant effect on the concentrations of Mg, K and Ca, except for Na. The effect of HA in the mixtures on ammonia loss was related to their effect on the formation of ammonium over ammonia. Conclusion: Surface-applied urea fertilizer efficiency could be increased when coated with 1.00 g of HA.